The Recognition of a Diarylimine as a Metabonate Produced During Incubation of N‐Benzyl‐4‐chloroaniline with Hepatic Microsomal Preparations - (:unkn) unknown (My University, 1994)
Abstract— Evidence is presented for the formation of N‐benzylidene‐4‐chloroaniline as a metabonate during the metabolism of N‐benzyl‐4‐chloroaniline. Control studies suggest that the diarylimine is formed as a chemical artifact from the debenzylation products (benzaldehyde and 4‐chloroaniline). This novel observation indicates a possible pathway to amide formation from N‐benzylanilines via diarylimines as intermediates. 1994 Royal Pharmaceutical Society of Great Britain